Limit load based evaluation of plastic ? factor for C(T) specimen with a mismatched weld - R. Nikhil; S.A. Krishnan; G. Sasikala; A. Moitra (Fracture and Structural Integrity)
Plastic ? factor is adopted to account for crack tip plasticity while evaluating the fracture toughness of the materials as per ASTM E1820. It is valid only for homogeneous materials. The plastic ? factor for Compact Type (C(T)) geometry with type 316LN stainless steel weld has been evaluated based on elastic-plastic FE analysis. The incremental elastic-plastic material model with various values for strength mismatch ratio (M) i.e. ratio of yield strength of weld metal to that of base metal, from 1.2 to 2.2 have been considered. The weld width (h) parallel to the crack plane is varied from 4 mm to 16 mm. The ? values thus obtained are analyzed and the inferences are discussed.